1987
DOI: 10.1093/nar/15.6.2593
|View full text |Cite
|
Sign up to set email alerts
|

The length but not the sequence of the polyoma virus late leader exon is important for both late RNA splicing and stability

Abstract: ABSTRACT'Polyoma virus late RNA processing provides a convenient model system in which to study the mechanics of splicing in vivo. In order to understand further the role of the untranslated "late leader" unit in late RNA processing we have constructed a group of polyoma viruses with deletions and substitutions in the leader exon. This has allowed us to determine that there is a minimum exon size required for both pre-mRNA splicing and stability in this system. We show here that the non-viability of a mutant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 50 publications
5
20
0
Order By: Relevance
“…Cytoplasmic RNA made from this construct was compared with wild-type RNA in an RNase protection assay which detected early spliced species (as an internal control for transfection efficiencies and RNA amounts) and late Vispliced species. Such an assay has been reported in other work from our laboratory (4,7). The results are shown in Fig.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Cytoplasmic RNA made from this construct was compared with wild-type RNA in an RNase protection assay which detected early spliced species (as an internal control for transfection efficiencies and RNA amounts) and late Vispliced species. Such an assay has been reported in other work from our laboratory (4,7). The results are shown in Fig.…”
supporting
confidence: 69%
“…1 In the 1-13 and I-11 lanes the upper band is intermediate in size from that representing two tandem Li exons (lane [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] or two tandem L2 exons (lane Py), indicating that the shorter Li had spliced to wild-type-length L2. Thus, Li and L2 exons can splice to each other in long primary transcripts, with a terminal splice to a body exon.…”
mentioning
confidence: 99%
“…Previous results from our laboratory have shown that mutations that destabilize the late-strand transcripts result in increased expression of the early-strand RNAs (28,55,56). An example of this antisense-induced regulation is shown in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…A polyadenylated subset is processed by leader to leader splicing, generating mature transcripts with a single mRNA body sequence, and multiple copies of a 57-nt leader (3,5,10,13,28,32,34,38,44). Leader-to-leader splicing, and hence the synthesis of giant late transcripts, plays an important role in the generation of a stable mature 16S VP1 mRNA (4,5). The exact fate and role of the early giant RNA remain to be determined.…”
Section: Discussionmentioning
confidence: 99%